Lessons to be Learned for Gastroenterology from Recent Issues in Clinical Trial Methodology - C Ohmann; J Albrecht (Canadian Journal of Gastroenterology)
Randomized trials are the preferred tool for patient-oriented research, and their main role is to enable the transfer of results from basic research to routine application. While the need for randomized trials is evident, conducting these trials is becoming increasingly difficult and complex. This article reviews actual and conflicting issues of clinical trials with respect to gastroenterology. Major problems in trial design are neglect of previous research, inadequate sample size calculations and irrelevant outcome criteria. Significant trial management problems include subversion of random allocation, and the design of systems and procedures that are inefficient, ineffective and inflexible. One of the major challenges in conducting randomized, controlled trials is obtaining informed consent because of the differing perspectives and languages of physicians and patients. Recommendations include practical guidance in obtaining informed consent, feedback of trial results to patients and support of research related to obtaining informed consent. Despite statistical guidance, several critical issues persist with respect to trial analysis. The use of confidence intervals is under-represented, the presentation of baseline data is often omitted and postsubgroup analysis is performed. Another controversial but relevant issue is the intention-to-treat analysis. Despite the formulation of standards, there is consistently poor quality of trial reporting, poor registration of unpublished trials and limited registration of ongoing trials. The authors conclude that there is a need for more randomized trials in gastroenterology. While the complexity of trial conduction has increased, so have the means of methodological and practical support. Thus, all problems can be professionally tackled, resulting in good clinical research.